Navigating the Oesophagus: Case Series on Tackling Complications Post-Esophagectomy in Achalasia Patients - Yazfa, Aminath; Kosai, Nik Ritza; Ubaid, Abdulla; Ali, Aishath Azna; Choudhury, Chishti Tanhar Bakth (British Journal of Healthcare and Medical Research, 2025)
Achalasia, a primary esophageal motility disorder, manifests as impaired peristalsis and dysfunctional relaxation of the lower esophageal sphincter. Treatment aims to alleviate the functional obstruction at the gastroesophageal junction, facilitating esophageal emptying. For end-stage cases, esophagectomy is often recommended as the primary intervention, despite the considerable postoperative complications it entails. In this case series, we present instances of various complications post-McKeown’s esophagectomy in achalasia patients with sigmoid oesophagus. These complications encompass anastomotic strictures, leaks, hydrothorax, tracheal injury, and laryngeal nerve damage.